2016
DOI: 10.1186/s12974-016-0660-1
|View full text |Cite
|
Sign up to set email alerts
|

Class I PI3K inhibitor ZSTK474 mediates a shift in microglial/macrophage phenotype and inhibits inflammatory response in mice with cerebral ischemia/reperfusion injury

Abstract: BackgroundMicroglia/macrophages play a critical role in the inflammatory and immune processes of cerebral ischemia/reperfusion injury. Since microglia/macrophages can reversibly shift their phenotype toward either a “detrimental” or a “restorative” state in the injured central nervous system (CNS), compounds mediate that shift which could inhibit inflammation and restore the ability to alleviate cerebral ischemia/reperfusion injury would have therapeutic potential.MethodsTransient middle cerebral artery occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Studies of other IRI conditions in the CNS suggest a strong correlation between IRI, inflammation, and neurological recovery. For example, PI3K inhibition resulted in altered microglia activation, decreased production of inflammatory cytokines, and improved neurological outcomes in a cerebral IRI model (65). However, it is worth noting that activation of the immune system and astrocytes is not always detrimental and should not be entirely abolished.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of other IRI conditions in the CNS suggest a strong correlation between IRI, inflammation, and neurological recovery. For example, PI3K inhibition resulted in altered microglia activation, decreased production of inflammatory cytokines, and improved neurological outcomes in a cerebral IRI model (65). However, it is worth noting that activation of the immune system and astrocytes is not always detrimental and should not be entirely abolished.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Wang and co-workers found that in male C57BL/6 mice ZSTK474, an inhibitor of PI3K had a neuroprotective action because it mitigated cerebral ischemic/reperfusion injury by fostering a beneficial microglial/macrophage phenotype [102].…”
Section: Therapeutic Strategies On the Modulation Of Pi3k Signalingmentioning
confidence: 99%
“…Fc receptor-mediated phagocytosis and phagocytic uptake of apoptotic cells is dependent on the activation of phosphoinositide 3-kinase (PI3K) [68]. A PI3K inhibitor decreased expression of CD16 on microglial cells (central nervous system-resident macrophages), suggesting a link between PI3K signalling and Fc receptor expression [69]. Although seasonal H1N1 and H3N2 IAV activate the PI3K signalling pathway in mouse AMs, an H5N1 IAV fails to do the same in infected epithelial cells [70,71].…”
Section: Iav Replication and Macrophage Phagocytosismentioning
confidence: 99%